2017
DOI: 10.1073/pnas.1614654114
|View full text |Cite
|
Sign up to set email alerts
|

Origin of microbial biomineralization and magnetotaxis during the Archean

Abstract: Microbes that synthesize minerals, a process known as microbial biomineralization, contributed substantially to the evolution of current planetary environments through numerous important geochemical processes. Despite its geological significance, the origin and evolution of microbial biomineralization remain poorly understood. Through combined metagenomic and phylogenetic analyses of deep-branching magnetotactic bacteria from the Nitrospirae phylum, and using a Bayesian molecular clock-dating method, we show h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 70 publications
5
124
0
1
Order By: Relevance
“…Recently, Lin and colleagues () proposed that magnetotaxis in MTB developed during the Archean, suggesting that magnetoreception and the Earth's magnetic field evolved together over time. Understanding the origin and evolution of magnetoreception is clearly important in understanding mechanisms of magnetoreception currently utilized by organisms and possibly to predict future developments in this area, especially in view of the recent unexpected changes in Earth's magnetic field (Witze, ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Lin and colleagues () proposed that magnetotaxis in MTB developed during the Archean, suggesting that magnetoreception and the Earth's magnetic field evolved together over time. Understanding the origin and evolution of magnetoreception is clearly important in understanding mechanisms of magnetoreception currently utilized by organisms and possibly to predict future developments in this area, especially in view of the recent unexpected changes in Earth's magnetic field (Witze, ).…”
Section: Introductionmentioning
confidence: 97%
“…In sediments or water column, MTB are markers of oxic/anoxic transition zones (OATZ) where the concentration of dissolved iron is at its maximum (Kopp and Kirschvink, 2008;LefĂšvre and Bazylinski, 2013). MTB have been proposed to represent some of the most ancient organisms capable of biomineralization, with an origin dating back to at least 3 Ga (Lin et al, 2017). Although MTB are ubiquitous on Earth, their impact on the past and modern biogeochemical cycling of metallic elements is still poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Being one of the deep-branching MTB group, Nitrospirae MTB plays an important role when analysing the origin and evolution of magnetosome biomineralization and magnetotaxis. Lin et al suggested that the magnetosome biomineralization and magnetotaxis was present before the separation of the Nitrospirae and Proteobacteria phyla, which was between~3.38 and 3.21 Ga (Lin et al, 2017b). However, it remains unclear whether the acquisition of magnetosome island (MAI), that encodes essential proteins for magnetosome biosynthesis in the genome, occurred before or after the divergence between freshwater and marine Nitrospirae MTB.…”
Section: Phylogenetic Analysismentioning
confidence: 99%